Rozkład naprężeń w nieskończonej płycie złożonej - Chakrabarti, S.K. (Engineering Transactions, 1968)
The expressions for stresses and displacements in two semi-infinite isotropic plates connected together, having different elastic properties and acted on by a ouple at any point inside one of them, have been obtained in this paper.